The herbaceous flora of Ulu Endau, Johore-Pahang, Malaysia, including taxonomic notes and descriptions of new species - Kiew, Ruth (Malaysian Nature Society, 1987)
The herbaceous flora of Ulu Endau is as diverse as other areas in Malaysia with the Cyperaceae, Zingiberaceae, Gesneriaceae, Melastomataceae, Araceae, Rubiaceae and Acanthaceae being the predominant families, and Didymocarpus, Sonerila, Dischidia, Fimbristylis and Mapania being the predominant genera specieswise. The flora also shows several interesting features such as a dearth of Begonia species, an affinity with the flora of the east coast (Pahang and Trengganu), and the presence of species endemic to Johore and specifically to the Ulu Endau area. A checklist of herbaceous species is provided together with notes on their habitat, abundance and distribution. New species described are Codonobo ea nivea, Didissandra kiewii, Didymocarpus craspedodromus, D. falcatus and Loxocarpus tunkui (Gesneriaceae) and Phyllagathis stolonifera (Melastomataceae). Paraboea caerula and Didymocarpus azureus are synonyms of D. densifolius, and D. perdita is a synonym of D. puncticulatus.